The relationship of children's concern and the couple's empty-nest stress experiences with their relationship purpose - Cabarles, Irene Grace S.
This corretional study aimed to find out whether the degree of children's concern for their parents and the empty-nest stress experiences of these parents have an effect on their relationship purpose.